Peer to peer file sharing in music works; is it an intrusion to copyright? case study of Tanzania - Mrutu, Mercy Ezekiel (Centre for Law and Society, 2026)
The dissertation critically analyses the effect of peer to peer file sharing in music copyright. Traditionally Copyright law was meant for material or physical works, however, with the development in Information and Computer technology and later digital technology, copying has been made simple and more efficient. As a result, people can now get copyrighted works through peer to peer file sharing, regardless of whether such practice infringe or does not infringe owners exclusive rights. Various countries have taken various steps including amendment of relevant copyright laws and through case decisions in order to balance between users' interests and interests of copyright holders for purposes of making such laws up to date. This study analyses various approaches undertaken by the United States of America and European Union in order to find out how their copyright law developed and addresses issues of digital copyright infringements of music through peer-to-peer file sharing and draw lessons for Tanzania. The interest to carry out this study was intensified by the extent of the problem after discovered that currently music is easily and freely transferred through peer to peer file sharing and at times owners of copyright are not considered through such music transfer. This study assed the current legal position of Tanzania in respect of peer to peer file sharing and assessed whether it provides for music copyright infringement through peer to peer file sharing. The study further reviewed the position of United States of America and European Union in order to make out how their legal framework addressed the problem of peer to peer file sharing in music copyright. The finding of this research was obtained through library research. Findings of this research revealed that the Copyright and Neighboring Rights Act, No 7 of 1999 of Tanzania does not specifically provide for electronic copyright infringement and consequently for music copyright infringement through peer to peer file sharing.